Comparison of BOLD and CBV using 3D EPI and 3D GRASE for cortical layer functional MRI at 7 T. Issue 6 (18th June 2020) - Beckett, Alexander J. S.; Dadakova, Tetiana; Townsend, Jennifer; Huber, Laurentius; Park, Suhyung; Feinberg, David A.
Abstract : Purpose: Functional MRI (fMRI) at the mesoscale of cortical layers and columns requires both sensitivity and specificity, the latter of which can be compromised if the imaging method is affected by vascular artifacts, particularly cortical draining veins at the pial surface. Recent studies have shown that cerebral blood volume (CBV) imaging is more specific to the actual laminar locus of neural activity than BOLD imaging using standard gradient‐echo EPI sequences. Gradient and spin‐echo (GRASE) BOLD imaging has also shown greater specificity when compared with standard gradient‐echo EPI BOLD. Here we directly compare CBV and BOLD contrasts in high‐resolution imaging of the primary motor cortex for laminar functional MRI in four combinations of signal labeling, CBV using slice‐selective slab‐inversion vascular space occupancy (VASO) and BOLD, each with 3D gradient‐echo EPI and zoomed 3D‐GRASE image readouts. Methods: Activations were measured using each sequence and contrast combination during a motor task. Activation profiles across cortical depth were measured to assess the sensitivity and specificity (pial bias) of each method. Results: Both CBV imaging using gradient‐echo 3D‐EPI and BOLD imaging using 3D‐GRASE show similar specificity and sensitivity and are therefore useful tools for mesoscopic functional MRI in the human cortex. The combination of GRASE and VASO did not demonstrate high levels of sensitivity, nor show increased specificity. Conclusion: Three‐dimensional EPI with VASO contrast and 3D‐GRASE with BOLD contrast both demonstrate sufficient sensitivity and specificity for laminar functional MRI to be used by neuroscientists in a wide range of investigations of depth‐dependent neural circuitry in the human brain.